Osobennosti gemodinamiki v nizhnykh konechnostyakh u sportsmenov razlichnoj spetsializatsii - Zusmanovich, F. N.; Gryaznikh, V. A.; Elizarova, S. N.; Solomka, O. V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The research was carried out with 41 elite athletes (21 skiers and track and field athletes and 20 wrestlers. It was found out that all people irrespective of training level had the higher index of systolic blood pressure on thigh and shin in comparison with shoulder. This difference was shown to the great extent with the wrestlers. By the track and field athletes it was not so noticeable. The dimensions of extremities trunk arteries and the speed of blood flow volume were higher in the track and field athletes and less in the wrestlers. The revealed features of regional hemodynamics display the specific time and power features of athletes' work. They can be used for the evaluation of the athletes' training level.